Editorial introduction - Jermaine S. McDougald (Universidad de La Sabana, 2014)
Welcome to Volume 7, Issue 2 of the Latin American Journal of Content and Language Integrated Learning (LACLIL). This issue offers insights from researchers on areas related to didactic transposition, vocabulary and gender variation, teacher training, CLIL implementation, vocabulary assessment and CLIL with Spanish as a foreign language. Researchers from a variety of contexts -Argentina, and Spain, as well as different parts of the United States-with a variety of leaners (primary, secondary, and tertiary education), share how CLIL has been working in their context. More and more practitioners are increasingly looking at the multiple ways in which CLIL can be implemented in accordance with their contexts, which serves an indicator that CLIL is starting to make a difference in more educational contexts worldwide.